Eksopolisakarida dari Lactobacillus sp. Isolat Susu Kuda Sumbawa dan Potensinya sebagai Prebiotik (EXOPOLYSACCHARIDES FROM LACTOBACILLUS SP. ISOLATED FROM SUMBAWA MARE’S MILK AND ITS POTENTIAL APPLICATION AS PREBIOTICS) - Sujaya, I Nengah; Aryantini, Ni Putu Desy; Nursini, Ni Wayan; Cakrawati, Cok. Istri Dewiyani; Juliasari, Ni Luh Made Ema; Dwipayanti, Ni Made Utami; Ramona, Yan (Jurnal Veteriner; Vol 13 No 2 (2012), 2013)
This research aimed to isolate exopolysaccharides (EPS) producing Lactobacilli isolated fromsumbawa mare’s milk and its potential as prebiotics for modulating the growth of Bifidobacteriumbreve. Nine strains of Lactobacillus sp. were screened for their capabilities to produce EPS usingmodified MRS medium containing sucrose. Prebiotics potential of the EPS was verified by culturingB. breve JCM1273 in TOS medium containing EPS. The results showed that all strains ofLactobacillus sp. produced EPS on MRS sucrose medium and two strains (Lactobacillus SK3.1 andLactobacillus SK4) produced more EPS compared to the other strains tested. Bifidobacteriumbreve JCM1273 showed weak activity while in direct metabolism of EPS produced by Lactobacillussp. SK4 and its growth was enhanced on acid hydrolyzed EPS. Since this phenomenon mighthappened when the EPS exposed by the low pH during gastric passage, hence the EPS might be apotential source to be developed as prebiotics. Nevertheless, further investigation is necessary toevaluate the bifidogenic affects of EPS in Lactobacillus sp. SK4.
Keywords: Lactobacillus, exopolysaccharides, sumbawa mare’s milk, prebiotic